APQP: caracterização da aplicação da metodologia de gestão de desenvolvimento de produtos em fornecedores dos setores de linha branca e automotivo - Pimenta, Laura Cunha Neto (2009)
The exchange of knowledge and optimization of resources optimism are increasingly needed necessaries for companies´ Product Delevopment Process (PDP). The Product Quality Advanced Planning (APQP) is a structured method, contained in Norm ISO/TS 16:949:2002, which aims to define and execute the actions required for a PDP in order to ensure that the product satisfies the customer. It´s greatest contribution is to facilitate communication among all people and activities. Although the APQP has been used primarily by the automotive industry, the possibility to apply this method for the white goods industry is considered, mainly due to this industry has been precursor of many methods, such as lean production. Furthermore, the search for a developing standardized products method could facilitate the work of automotive and white goods suppliers. The lean production has also contributed to the optimization of resources and administrative proceedings in these industries. Thus, this standardized method could include the use of some lean production tools. The aim of this work is to characterize the use of APQP in white goods and automotive industries suppliers and more specifically, to evaluate the possible failures in these suppliers product development process, and to discuss the importance of tools in each step of APQP and the application of these to white goods industry. The hypotheses were made concerning the possible simplification of this standard method, the integration of areas, the knowledge obtained in the implementation of APQP and facilities of lean production and six sigma for the implementation of APQP. The chosen method for this work was the description of five case studies made in companies of the electro electronic and chemical fields, which are suppliers of both industries cited. In these companies a representative of the automotive and one of white goods industry were interviewed. The research finds that it´s possible to use the APQP method in the white goods as well as it shows white goods companies which have already requested it to suppliers. It also describes the PDPs of each company, highlights the major failures in the methods used and describes an overview of the automotive and white goods industries PDPs. A proposal to APQP application with some lean production tools is presented in the final chapters.